2014
DOI: 10.1590/s0100-69912014000300010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the celexoxib in microscopic changes of the esophageal mucosal of rats induced by esofagojejunostomy

Abstract: celecoxib had neither protective nor inducing effect on esophagitis, but had a protective effect on dysplasia of the animals of group I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Some authors have reported that non-steroid anti-inflammatory drugs promote intestinal healing, while others have shown their deleterious effects on intestinal healing by increasing the rate of anastomotic dehiscence which consequently leads to a higher mortality rate [1][2][3][4] . Also herbal medicines from Amazon region in…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that non-steroid anti-inflammatory drugs promote intestinal healing, while others have shown their deleterious effects on intestinal healing by increasing the rate of anastomotic dehiscence which consequently leads to a higher mortality rate [1][2][3][4] . Also herbal medicines from Amazon region in…”
Section: Introductionmentioning
confidence: 99%